PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN KELAS V SDN 4 PRINGGABAYA TAHUN AJARAN 2020/2021 - Alfan Hadi; Nasaruddin Nasaruddin; Husniati Husniati (Program Studi PGSD, FKIP, Universitas Mataram, 2020)
Be a teachers can choose and use teaching methods that purpose to improve the quality of teaching, so that the learning process effectively. In a cooperative learning approach to the type of STAD is one type of cooperative learning the most simple that can be used by teachers who use cooperative approach. Based on the description above, the problem in this study is there an effect of the STAD learning model on student learning outcomes. The purpose of this study was to determine the effect of STAD on student learning outcomes. This research method uses a quantitative approach with an experimental design, the type of quasi experimental design nonequivalent control group. The analysis, 6 students complete with 24% of cognitive, the Psychomotor completed 3 students 12%. After being given treatment, the learning outcomes become 20 student completed with 80% of cognitive, the psychomotor completed by 17 students with 68%. Thus the STAD type of cooperative learning model can improve student learning outcomes